Leuprorelin‐Induced Thrombocytopenia Successfully Treated With Surgical Resection of the Injection Site - Ryota Mori; Satoru Taguchi; Masahiro Yamamoto; Yuta Inoue; Koichiro Kanazawa; Yoichi Fujii; Haesu Lee; Kiichi Furuse; Hiroaki Maki; Jun Kamei; Shigenori Kakutani; Yuta Yamada; et al. (IJU Case Reports)
ABSTRACT Introduction Drug‐induced thrombocytopenia (DITP) can be caused by many kinds of drugs. Its treatment generally involves discontinuation of the responsible drug. Case Presentation A 70‐year‐old man received a subcutaneous injection of long‐acting (24‐week) leuprorelin depot as androgen deprivation therapy for prostate cancer. Four days after the injection, he presented with gingival bleeding and his platelet count was remarkably decreased (< 1000/μL). There was no sign of malignancy but the presence of megakaryocytes on bone‐marrow examinations. Considering immune and/or DITP, he started immunoglobulin and steroid therapy while stopping all suspected medications. However, even a month later, his platelet count did not recover with the need for frequent platelet transfusions. Therefore, he eventually underwent surgical resection of the leuprorelin injection site. After the surgery, his platelet count drastically recovered and platelet transfusion became unnecessary. Conclusion We report a case of leuprorelin‐induced thrombocytopenia that was successfully treated with surgical resection of the injection site.